Viability of cash waqf models under the Nigerian law: an appraisal - Ishola, Abdullahi Saliu; Syed Abdul Kader, Sharifah Zubaidah; Ansari, Abdul Haseeb (Serials Publications(P)LTD, 2016)
Cash awkaf (plural of waqf ) have been a well-recognised tool for social development of Muslims in various countries wherever they are being practiced. It is governed by set of Islamic principles pertaining to awqaf converted by some countries into legislation. In those countries, they have proven to be one of the tools for social welfare and alleviation and ultimate eradication of poverty, based on the will of the waqeefs. In order to serve the purpose of their creation, it is better if the waqf money is allowed to be invested in the interest of the beneficiaries and growth of the awqaf. There are a number of legal issues pertaining to administration of cash waqf, which are yet to be addressed. The existing literatures on cash waqf also do not have definite answers to them. In Nigeria, cash waqf is not well in practice. Because of this reason, there is lack of a legal framework on it. The paper reviewed the existing literatures on cash waqf, but they are not dealing with it in the context of Nigeria. The paper presents an appraisal of the papers reviewed.